2017
DOI: 10.3390/ijerph14080839
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators of Physical Activity: Voices of Adolescents in a Disadvantaged Community

Abstract: Despite increasing socioeconomic inequalities in the health and well-being of adolescents, the voices of adolescents in disadvantaged communities regarding facilitators of physical activity (PA) have received relatively little attention. In response, the purpose of this study was to illuminate what adolescents in a multicultural community of low socioeconomic status (SES) in Sweden convey concerning facilitators of PA. Adolescents (n = 53, aged 12–13 years) were recruited from a school in a multicultural commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 35 publications
5
41
0
5
Order By: Relevance
“…These factors were also identified in previous studies [2528, 31]. In literature, competition is often considered as a barrier to adolescents’ PA especially among girls and those lacking skills or physical conditions [25, 26, 28, 46]. In our study, competition was perceived as a facilitator for PA by some participants, which were almost exclusively boys.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These factors were also identified in previous studies [2528, 31]. In literature, competition is often considered as a barrier to adolescents’ PA especially among girls and those lacking skills or physical conditions [25, 26, 28, 46]. In our study, competition was perceived as a facilitator for PA by some participants, which were almost exclusively boys.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to previous studies, adolescents with physical disability [47] and/or with poor physical condition and skills [25, 27, 28, 31, 46] engage in less PA than their normal peers. In a systematic review, Carlon et al found that youth with cerebral palsy participated in 13 to 53% less PA than their peers and were more sedentary [47].…”
Section: Discussionsupporting
confidence: 83%
“…The other studies that analyzed the effects of physical activity on adolescents reported effective results for the improvement of health conditions; 36 , 37 however, the need to determine the quality of physical education classes, stimulating the practice of pleasant and fun physical activities, without competitive or performance-based guidance, is brought about 38 . Healthy lifestyle habits, such as physical activity practice and quality food consumption are also encouraged through educational support, so that behavioral changes are sustainable and related to the construction of intrinsic motivation to maintain the desired behavior until adulthood 33 …”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are needed to understand the consequences of appreciative inquiry as this strength-based focus may appear to be obvious, creating a risk of it being taken for granted. Additionally, we would like to echo Jonsson et al (2017) stressing the importance of an environment supporting physical activity in which schoolchildren can satisfy their needs for autonomy, competence, and relatedness. Currently, the findings from this study are being implemented in a health-promoting intervention using children's active school transportation.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%